2022
DOI: 10.1111/jav.03051
|View full text |Cite
|
Sign up to set email alerts
|

Nest‐boxes alter the reproductive ecology of urban cavity‐nesters in a species‐dependent way

Abstract: To mitigate the shortage of natural breeding sites in cities, nest-boxes are provided for cavity-nesters. However, these are not the breeding sites these animals originally evolved in and optimised their breeding performance to. It thus remains inconclusive if nest-boxes can provide adequate substitutes, ensuring equivalent fitness returns for breeding animals. Additionally, the majority of knowledge on the ecology of urban birds comes from nest-box populations, but no study to date directly compared fitness c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 81 publications
5
34
0
Order By: Relevance
“…Importantly, the small distance ascertained that the plots were functionally identical as they shared the same environmental patch. Accordingly, Sudyka et al (2022a) found no difference in food availability between study plots in both field seasons, assesses by widely used method of frass fall collection (Wesołowski & Rowiński, 2014). Ambient temperature and humidity as well as anthropogenic factors (noise and air pollution, measured as PM 2.5 concentration) were found to be uniform between study plots (Sudyka et al, 2022b).…”
Section: Study Site and Samplingmentioning
confidence: 77%
See 4 more Smart Citations
“…Importantly, the small distance ascertained that the plots were functionally identical as they shared the same environmental patch. Accordingly, Sudyka et al (2022a) found no difference in food availability between study plots in both field seasons, assesses by widely used method of frass fall collection (Wesołowski & Rowiński, 2014). Ambient temperature and humidity as well as anthropogenic factors (noise and air pollution, measured as PM 2.5 concentration) were found to be uniform between study plots (Sudyka et al, 2022b).…”
Section: Study Site and Samplingmentioning
confidence: 77%
“…However, as nonsignificant, it was dropped from all models. In the final models, the following variables of biological relevance were always retained: cavity type, parental colour metrics (to quantify parent-offspring correlations), nestling sex and year (differences in weather conditions and food availability between two study seasons, (Sudyka et al, 2022a). Other factors (parental age, lay date, clutch size, nestling mass), if nonsignificant, were removed from the models in backward elimination procedure (Quinn & Keough, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations